Studies on the microbial load of cryopreserved Murrah semen - SHUKLA, M K; MISRA, A K; GUPTA, H P; SINGH, S P (The Indian Journal of Animal Reproduction, 2023)
The objective of the present study was to detennine microbial load in frozen semen of three Murrah bulls using ten ejaculatesfrom each bulls. The average bacterial load determined using pour plate method in the frozen semen of the three bulls was 79.00±0.76,7.00±0.91 and 60.00±0.87, respectively with an overall mean of 48.60±0.73 colony forming units (CFU) m1·1• The SPC differedsignificantly (P< 0.01) between the three bulls. All the semen samples were found to be negative for fungus, mucor and yeast.
Keywords: Buffalo; semen; microbial load; standard plate count